Computer-aided engineering analysis for the performance augmentation of a fin-tube heat exchanger using vortex generator. (March 2020) - Gupta, Sachin; Roy, Aditya; Gupta, Arvind
The heat transfer performance of fin-tube heat exchangers can be enhanced with the help of longitudinal vortex generators. In this work, we investigate the effect of employing a rectangular winglet having a punched hole on heat transfer and flow resistance characteristics in a fin-tube heat exchanger with the help of numerical simulations. Studies were performed on two configurations, namely, common flow down and common flow up at upstream and downstream locations. Performance characteristics such as Colburn's factor ( j ), friction factor ( f ), and performance evaluation criterion were considered for evaluating the thermohydraulic performance. Investigations were performed considering Reynolds number in the range of 1500–9000, keeping the angle of attack as 45°. The shear stress transport k-ω turbulence model was used for performing numerical simulations. A significant augmentation of up to 71% in the thermohydraulic performance of fin-tube heat exchanger was observed with the common flow down configuration located upstream over the common flow up configuration located upstream, which displayed the least improvement.